Desain Interior Kantor Click Indonesia Global Dengan Konsep Scandinavian - Refan Widi Putra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This design aims to design the interior of the Click Indonesia Global office using the Scandinavian concept, which is expected to enhance employee comfort and productivity. The research background focuses on the need for a workspace that supports employee activities in the modern era, which is increasingly dynamic and complex. The method used in this study is the 4D approach (Define, Design, Develop, Disseminate) with a SWOT analysis to identify strengths, weaknesses, opportunities, and threats in the design. The research findings indicate that the application of the Scandinavian concept, with a dominance of neutral colors and the use of natural materials, can create a more comfortable, aesthetic, and efficient working environment. The implications of this study are expected to serve as a reference for developing office interior designs that are not only functional but also support overall employee well-being.